2003
DOI: 10.1159/000071895
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Antibody Responses to Influenza Vaccination in the Elderly following a Cognitive-Behavioural Stress Management Intervention

Abstract: Background: Previous research has demonstrated that the psychological morbidity experienced by informal caregivers is associated with increased vulnerability to infectious diseases, in particular influenza. A pragmatic trial was conducted to examine whether a stress management intervention (SMI) could reduce psychological morbidity and enhance the antibody response to influenza vaccination in the elderly, and whether changes in immune response of SMI participants were associated with hypothalamic-pituitary-adr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…In a study of caregivers of spouses with dementia, those who participated in an 8-week stress management group showed greater immune protection following influenza vaccination than controls [97]. Similarly, among 48 healthy adults, those who completed an 8-week meditation intervention exhibited better antibody responses to the flu shot as compared to wait-list controls [98].…”
Section: Interventions To Improve Antibody Responses To Vaccinationmentioning
confidence: 99%
“…In a study of caregivers of spouses with dementia, those who participated in an 8-week stress management group showed greater immune protection following influenza vaccination than controls [97]. Similarly, among 48 healthy adults, those who completed an 8-week meditation intervention exhibited better antibody responses to the flu shot as compared to wait-list controls [98].…”
Section: Interventions To Improve Antibody Responses To Vaccinationmentioning
confidence: 99%
“…Psychological stress, infection-induced stress, and chemically induced oxidative stress have been associated with decreased antibody levels in both animal models of infection and in various human populations (4,18,61). Moreover, considerable evidence indicates that redox signaling, oxidative stress, and cellular antioxidant levels can influence the function of each of the cell types (antigen-presenting cells, T cells, and B cells) regulating immunogenicity and their roles in IgG synthesis.…”
Section: Serum 8-isoprostane Related To Serum Igg Antibody Levelsmentioning
confidence: 99%
“…Cronbach > values for these scales in the present study ranged from 0.77 to 0.92. Participants also rated on a 0-to 5-point Likert scale the amount of exercise, fruit and vegetable intake, vitamin intake, alcohol consumption, and frequency of adequate sleep (from never [0], once a month [1], once a week [2], two to three times a week [3], four to five times a week [4], and every day [5]) and indicated the number of cigarettes smoked per day over the last month.…”
Section: Emotional Distress and Health Behaviorsmentioning
confidence: 99%
“…They reported that their intervention was associated with enhanced antibody levels to influenza vaccination. Similarly, Vedhara et al (4) examined the effects of a stress management intervention on antibody responses to influenza vaccination in spousal carers of patients with dementia. Their intervention was associated with a significantly greater likelihood of the vaccine being effective: with protection against influenza (denoted by a four-fold increase in antibody levels) achieved in 50% of carers who received the intervention compared with only 7% of carers who did not receive the intervention and 29% of a noncarer control group.…”
Section: Introductionmentioning
confidence: 99%